Kajian faktor-faktor yang mempengaruhi pendapatan usahatani karet - Uliya, Uliya; Armando, Reno; Enita; Lamefa, Dina Yuliasty (PPPM STKIP PGRI Lamongan, 2025)
Analysis of Factors Affecting Rubber Farming Income in Mekar Jaya Village, Bajubang District. The objectives of this study are: (1) To determine the amount of rubber farming income in Mekar Jaya Village, Bajubang District (2) To determine the factors that affect rubber farming income. The study was conducted in April 2019. The sample taken in this study was 21 people. Based on the results of the study on income analysis that have been described previously, conclusions can be drawn. The conclusions are: (1) Rubber farming income. The income obtained by rubber farmers with a land area of ​​2.6 ha per farm earned an income of Rp. 37,372,666 / month and an average income per ha of Rp. 1,779,651 / month (2) The results of fertilizer cost data processing have a probability of 0.000, which indicates a positive influence of the production cost system on the income of rubber farmers. (3) Labor Testing. The results of labor data processing indicate a positive influence of the income system on rubber farmers. (4) Land Area Testing. The results of processing land area data show a positive influence of the income system and rubber farmers' income.